Effect of Disease Activity at Three and Six Months After Diagnosis on Long‐Term Outcomes in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. Issue 5 (28th March 2019) - Gopaluni, Seerapani; Flossmann, Oliver; Little, Mark A.; O'Hara, Paul; Bekker, Pirow; Jayne, David; ,
Abstract : Objective: The treatment of antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV) aims to suppress disease activity and prevent subsequent disease flare. This study sought to explore the association of early disease control with long‐term outcomes to validate early disease control as an end point for future clinical trials in AAV. Methods: Data from 4 European Vasculitis Society inception clinical trials in AAV (1995–2002) and subsequent data on long‐term outcomes from the trial data registry were studied. Clinical parameters in patients with AAV at baseline and at 3 and 6 months after diagnosis were assessed to study the long‐term risk of death and end‐stage renal failure (ESRF). At 6 months, outcomes were defined based on a disease status of either sustained remission (remission by 3 months, sustained to 6 months), late remission (remission after 3 months and by 6 months), relapsing disease (remission by 3 months but relapse by 6 months), or refractory disease (no remission by 6 months). Results: Of the 354 patients with AAV who were followed up for a median of 5.7 years, 46 (13%) developed ESRF, 66 (18.6%) died, and 89 (25.1%) had either died or developed ESRF. At 6 months, predictors of the composite end point of death or ESRF were as follows: age (hazard ratio [HR] 1.02, 95% confidence interval [95% CI] 1–1.05; P = 0.012), estimated glomerular filtration rate (HR 0.94, 95% CI 0.92–0.95; P < 0.001), and disease status at 6 months (late remission, HR 2.94, 95% CI 1.1–7.85 [ P = 0.031]; relapsing disease, HR 8.21, 95% CI 2.73–24.65 [ P < 0.001]; refractory disease, HR 4.89, 95% CI 1.96–12.18 [ P = 0.001]). Similar results were observed when these analyses were performed separately for death and for ESRF. Conclusion: The results of this study suggest that disease status at 3 and 6 months following the diagnosis of AAV may be predictive of the long‐term risk of mortality and ESRF, and therefore these may be valid end points for induction trials in AAV. The current findings need to be validated in a larger data set.